Jews out of the question : a critique of anti-anti-Semitism - Lapidot, Elʿad 1976- (SUNY series, philosophy and race, 2020)
"Argues that the opposition to anti-Semitism in contemporary political philsophy comes dangerously close to anti-Semitism itself"--